The Atomistic Understanding of the Ice Recrystallization Inhibition Activity of Antifreeze Glycoproteins - Wentao Yang; Yucong Liao; Qi Shi; Zhaoru Sun (Crystals, 2023)
As the most potent ice recrystallization inhibitors, antifreeze glycoproteins (AFGPs) have been extensively studied since their discovery. However, the molecular mechanism of how they inhibit ice growth remains controversial—notably, which group directly contributes to the binding of AFGPs to ice is hotly debated. Here, we use molecular dynamics simulations to investigate the atomistic details of the binding of AFGP8 to ice. We show that the binding of AFGP8 to ice can be divided into three cases: backbone dominant binding (BDB), disaccharide dominant binding (DDB) and weak binding (WB). Hydrogen-bonding and hydrophobic groups contribute equally to the binding of AFGP8 to ice and synergistically promote the binding. The –CH3 groups promote the contacting of AFGP8 to ice via hydrophobic effect, and the hydrogen-bonding groups anchor AFGP8 to ice surfaces through direct hydrogen bonding with ice. Specially, we verify that the -CONH- groups anchor the backbone of AFGP8 to ice by forming hydrogen bonds with ice surfaces while the –OH groups not only anchor the disaccharide to ice but also slow down the dynamics of the surrounding water. In addition, we reveal that both the backbone and the disaccharide can bind to ice surfaces while the latter is more flexible, which also perturbs the hydrogen bond network of potential ice-like water molecules by swaying in the solution to further enhance its antifreeze activity. This work provides the atomistic details of the ice growth inhibition mechanism of AFGP8, which is helpful for the design of high-efficacy cryoprotectants.